Tagging highly boosted top quarks - Schätzel, Sebastian; Spannowsky, Michael (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
For highly energetic top quarks, the products of the decay t→bqq′ are collimated. The three-prong decay structure can no longer be resolved using calorimeter information alone if the particle jet separation approaches the calorimeter granularity. We propose a new method, the HPTTopTagger, that uses tracks of charged particles inside a fat jet to find top quarks with transverse momentum pT>1 TeV. The tracking information is complemented by the calorimeter measurement of the fat jet energy to eliminate the sensitivity to jet-to-jet fluctuations in the charged-to-neutral particle ratio. We show that with the HPTTopTagger, a leptophobic narrow-mass Z′ boson of mass 3 TeV could be found using 300 fb−1 of 14 TeV LHC data.